Penerapan Model Project Based Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMA Negeri 1 Palangka Raya - Ernita Fransiska (Lembaga Pengembangan Kinerja Dosen, 2022)
This classroom action research aims to improve the critical thinking skills of Palangka Raya 1 Public High School students. Critical thinking skills are one of the skills developed in the 21st century. Critical thinking skills are honed so that students can practice rational reasoning, with an emphasis on making decisions about what to believe or do. This type of research is classroom action research. The research was carried out at SMA Negeri 1 Palangka Raya on the subject of Catholic Religion with material on the Church as Open Communion. The research subjects were class X students for the 2021/2022 academic year. The research instrument used a critical thinking skills questionnaire and observation of critical thinking skills in discussions. The data analysis technique uses a percentage formula. The results of this research are that in cycle I, of the 5 indicators of critical thinking skills, 3 indicators fall into the poor criteria and 2 indicators fall into the fairly good criteria. From the results of observations by colleagues who assessed the group's performance, 3 indicators fell into the fairly good criteria and 2 indicators fell into the not so good criteria. The score range comes in at a percentage of 55%-67%. In cycle II, of the 5 indicators of critical thinking skills, all indicators fall into very good criteria. From the results of peer observations, 5 indicators of critical thinking skills fall into very good criteria, namely in the range of 88% -92%.